Daring to think of the impossible: The story of Vlasiator - Palmroth, Minna (Frontiers in Astronomy and Space Sciences, 2022)
Vlasiator is the world’s first global Eulerian hybrid-Vlasov simulation code, going beyond magnetohydrodynamics in the solar wind – magnetosphere – ionosphere system. This paper gives the story of Vlasiator. An important enabler of Vlasiator is the rapid increase of computational resources over the last decade, but also the open-minded, courageous forerunners, who have embraced this new opportunity, both as developers but also as co-authors of our papers. Typically, when starting a new coding project, people think about the presently available resources. But when the development continues for multiple years, the resources change. If instead, one targets to upcoming resources, one is always in possession of a code which does not contain large legacy parts that are not able to utilize latest resources. It will be interesting to see how many modelling groups will take the opportunity to benefit from the current high-performance computing trends, and where are we in the next ten years. In the following, a simulation that directly handles and manipulates the phase space density f(r,v,t) is referred to as a Vlasov approach, whereas a simulation system that traces phase space samples by their kinetic characteristics of motion is a Particle-in-Cell approach. This terminology is consistent with its use in the magnetospheric simulation community.